THE INFLUENCE OF WORKLOAD, WORK ABILITY, AND JOB TRAINING ON EMPLOYEE PERFORMANCE AT PT SUMBER MAS INDAH PLYWOOD IN GRESIK - Ahmad Albara Dipayana; Sri Rahayu; Sundjoto; Rifda Fitrianty (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Workload, Work Ability, and Job Training on Employee Performance at PT. Sumber Mas Indah Plywood in Gresik. The research employs a quantitative approach with an associative research design. The population of this study consists of all employees of PT. Sumber Mas Indah Plywood in Gresik, while the sample is determined using a purposive sampling technique with a total of 61 respondents who work at the head office. Data collection techniques include questionnaire distribution using a Likert scale and documentation to support the research data. Data analysis techniques comprise data quality testing, classical assumption testing, multiple linear regression analysis, partial testing, simultaneous testing, and coefficient of determination analysis. The results indicate that Workload, Work Ability, and Job Training have a significant effect on Employee Performance, both partially and simultaneously, with Work Ability identified as the dominant variable, and most of the variation in Employee Performance can be explained by these three variables..